The poetry addict: Utz Rachowski as poet, political prisioner, and counselor - Stoehr, Louise; Stoehr, Ingo (Texto Poético, 2019)
Closely analyzing selected poems, this article traces the major phases of the five-decade-long career of contemporary German poet Utz Rachowski. First, East Germany’s paranoid repressive police force declared five of Rachowski’s poems to be subversive. Second, with his prison poems, Rachowski asserts his subjectivity against objectifying punishments. From this phase onward, the metaphor “poetry is a drug” helps us to understand the role of poetry for Rachowski. Third, his exile led to a sense of loss of home expressed in mature poetry. Finally, taking on responsibility for a dog during his 2012 stay in the United States reconfirmed Rachowski’s belief in trust, giving his poetry new productivity and a gentler tone. Outside his poetic career, Rachowski counsels people who have suffered under the state repressions ---------------------------------------------------------------------------- O POETA VICIADO: UTZ RACHOWSKI COMO POETA, PRISIONEIRO POLÍTICO E CONSELHEIRO Através da análise de alguns dos poemas de Utz Rachowski, este artigo descreve as principais fases de cinco décadas de sua carreira como poeta. Primeiro, analisamos como a força policial da Alemanha, paranoica e repressiva, declarou que cinco dos poemas de Rachowski eram subversivos. Em seguida, analisamos como os poemas de Rachowski sobre a prisão afirmam sua subjetividade contra a objetivação do castigo, no qual o autor usando a metáfora “a poesia é uma droga” ajuda os leitores a entender seus poemas. Mais adiante analisamos como o exílio levou Rachowski a ter uma sensação de perda, já que o mesmo perdeu o direito de ser livre em seu próprio país. E finalmente, discorremos sobre a fase em que Rachowski cuidou de um cachorro em 2012 nos Estados Unidos, o que o ajudou a restaurar sua confiança em relação à sociedade, dando a suas poesias uma nova produtividade e um tom mais suave. --- Original em inglês.